Highlights from NA61/SHINE: Proton Intermittency Analysis - Daria Prokhorova; Nikolaos Davis (Universe, 2019)
The NA61/SHINE experiment at CERN SPS searches for the critical point of strongly interacting matter via scanning the phase diagram by changing beam momenta (13A−150A GeV/c) and system size (p + p, p + Pb, Be + Be, Ar + Sc, Xe + La). An observation of local proton-density fluctuations that scale as a power law of the appropriate universality class as a function of phase space bin size would signal the approach of the system to the vicinity of the possible critical point. An investigation of this phenomenon was performed in terms of the second-scaled factorial moments (SSFMs) of proton density in transverse momentum space with subtraction of a noncritical background. New NA61/SHINE preliminary analysis of Ar + Sc data at 150A GeV/c revealed a nontrivial intermittent behavior of proton moments. A similar effect was observed by NA49 in “Si” + Si data at 158A GeV/c. At the same time, no intermittency signal was detected in “C” + C and Pb + Pb events by NA49, as well as in Be + Be collisions by NA61/SHINE. EPOS1.99 also fails to describe the power-law scaling of SSFMs in Ar + Sc. Qualitatively, the effect is more pronounced with the increase of collision-peripherality and proton-purity thresholds, but a quantitative estimate is to be properly done via power-law exponent fit using the bootstrap method and compared to intermittency critical index <semantics> ϕ 2 </semantics> , derived from 3D-Ising effective action.